2020
DOI: 10.1109/access.2020.3033279
|View full text |Cite
|
Sign up to set email alerts
|

Rural Financial Information Service Platform Under Smart Financial Environment

Abstract: With the continuous deepening of economic and social development and reform, the problems in rural financial development have gradually exposed. Therefore, in order to speed up the rural economic development and promote the construction of new rural areas. It is very necessary and urgent to promote the innovation of rural financial services and create a modern rural financial service platform. In order to solve the problems of information collection, processing and integration of rural financial information se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Economic environment factors are measured by regional economic development, the proportion of agriculture, agricultural labor productivity and convenience of commodity market transactions. Social environment factors include per capita education level, population density(T. Liu et al, 2020), and information technology (Dai, 2020). The descriptive statistics of influencing factors are shown in Table 2.…”
Section: Variables Of Influencing Factorsmentioning
confidence: 99%
“…Economic environment factors are measured by regional economic development, the proportion of agriculture, agricultural labor productivity and convenience of commodity market transactions. Social environment factors include per capita education level, population density(T. Liu et al, 2020), and information technology (Dai, 2020). The descriptive statistics of influencing factors are shown in Table 2.…”
Section: Variables Of Influencing Factorsmentioning
confidence: 99%
“…Since the 1980s, the theory of China's rural financial system has been fully developed, which relies entirely on market mechanisms and emphasizes that interest rate easing could boost financial intermediaries in rural areas. (Wensheng, 2020). After the 1990s, scholars found that social and non-market factors were essential for establishing efficient financial markets.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…In terms of the Self Organizing Map (SOM) for extracting features, Zhang et al suggested another unmonitored approach (Wensheng, 2020). This methodology included two essential developments, the retrieval of sub‐local images, as seen by their objectives of suspense and use of them from various angles, colouring, surface, and form.…”
Section: Background Ovarian Cancer Area Using Internet Of Medical Thingsmentioning
confidence: 99%